Shaping the new man : youth training regimes in Fascist Italy and Nazi Germany - Ponzio, Alessio (George L. Mosse series in modern European cultural and intellectual history., 2015)
Despite their undeniable importance, the leaders of the Fascist and Nazi youth organizations have received little attention from historians. In Shaping the New Man, Alessio Ponzio uncovers the largely untold story of the training and education of these crucial protagonists of the Fascist and Nazi regime, and he examines more broadly the structures, ideologies, rhetoric, and aspirations of youth organizations in Fascist Italy and Nazi Germany. Ponzio shows how the Italian Fascists' pedagogical practices influenced the origin and evolution of the Hitler Youth. He dissects similarities and differences in the training processes of the youth leaders of the Opera Nazionale Balilla, Gioventù Italiana del Littorio, and HItlerjugend. And, he explores the transnational institutional interactions and mutual cooperation that flourished between Mussolini's and Hitler's youth organizations in the 1930s and 1940s. -- from back cover.